2018
DOI: 10.11648/j.ijfsb.20180301.12
|View full text |Cite
|
Sign up to set email alerts
|

Functional Jam Production from Blends of Banana, Pineapple and Watermelon Pulp

Abstract: Functional jam from blends of banana, pineapple and watermelon pulp was produced and evaluated. The aim was to develop a locally but nutritionally rich, functional jam. Various blends of the fruit pulp were considered in order to select the best.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
3
0
4
Order By: Relevance
“…The decrease in these viscosities reflected less retrogradation tendency, which inhibited the staling rate of the biscuits(Wang et al, 2015). Recently,Yaqoob et al (2019) have reported that a decrease in FV might be due to the dis-aggregation of amylose molecules with the increased quantity of DPF in wheat flour(Yaqoob et al, 2019) Awolu et al (2018). reported similar findings of decreased SB when mango kernel seed flour was incorporated in wheat flour.…”
mentioning
confidence: 85%
“…The decrease in these viscosities reflected less retrogradation tendency, which inhibited the staling rate of the biscuits(Wang et al, 2015). Recently,Yaqoob et al (2019) have reported that a decrease in FV might be due to the dis-aggregation of amylose molecules with the increased quantity of DPF in wheat flour(Yaqoob et al, 2019) Awolu et al (2018). reported similar findings of decreased SB when mango kernel seed flour was incorporated in wheat flour.…”
mentioning
confidence: 85%
“…The absorbance of the extracted sample was measured at 335 nm. Finally, the content of vitamin A was calculated following the formula used by Olufemi Awolu . The Vit-C content was also determined using the previous method of Ochoa-Velasco et al with slight modifications.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Finally, the content of vitamin A was calculated following the formula used by Olufemi Awolu. 47 The Vit-C content was also determined using the previous method of Ochoa-Velasco et al 36 with slight modifications. The result was expressed as mg of AsA/100 g of the tomato sample.…”
Section: Methodsmentioning
confidence: 99%
“…Según las investigaciones realizadas, la composición varía de acuerdo con la naturaleza y proporciones de las frutas que componen la mermelada. En relación con las proteínas se han encontrado valores máximos de 7,45% en una mermelada compuesta por banana, sandía y piña (11) . El resultado obtenido 0.2380% son cercanos a los encontrados en mermeladas de arándanos (0,31%) (23) , piña (0,3%) (2), mamón y zarzamora (0,3%) (5), manzana de marañón (0,28%) (2) y uva (0,27%) (23) .…”
Section: Composición Nutricionalunclassified
“…A nivel mundial, numerosos países desarrollaron mermeladas combinando frutas de estación, es el caso de India con la mermelada de piña y banana (6) , en Perú sandía y arándanos (7) , arándano y frambuesa en Chile (8) , remolacha y mora en Ecuador (9) , piña y maracuyá en Ecuador (10), banana, piña y sandía en Nigeria (11) . En Paraguay, estas combinaciones se realizan a pequeña escala en zonas rurales, constituyéndose un atractivo de determinadas épocas y zonas.…”
Section: Introductionunclassified